Task-Shifting Echocardiography Training for Rheumatic Heart Disease Screening in Indonesia: A Feasibility Study - Dian Paramita Kartikasari; Achmad Lefi; Irawati Hajar Kikuko; Asri Laksitarini; Pandit Bagus Tri Saputra; Mahendra Eko Saputra; Diar Pasahari; Emildha Dwi Agustina (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Rheumatic heart disease remains a significant health concern in low-and middle-income countries, as it is often challenging to detect in its early stages due to subtle or absent symptoms, particularly during the subclinical phase. Task-shifting echocardiographic screening of RHD to GPs offers a scalable solution in low-resource settings.   Abstract Introduction: Rheumatic heart disease (RHD) remains a significant health burden in low- and middle-income countries. Early detection of RHD by trained general practitioners (GPs) enables earlier intervention to prevent disease progression. This study aimed to evaluate the feasibility and effectiveness of training non-expert health workers in Indonesia to perform echocardiographic screening for RHD, addressing the country’s unique challenges and bridging the gap in healthcare resources. Methods: A quasi-experimental pre-post intervention study was conducted involving 18 GPs with no prior echocardiography experience. The training consisted of one day of lecture-based instruction and six days of supervised hands-on practice. Knowledge was assessed using a newly developed RHD-echocardiography test that underwent face and content validation by two cardiologists and demonstrated good internal consistency (Cronbach’s alpha=0.82). Pre- and post-training knowledge was compared using paired t-tests. Diagnostic sensitivity and specificity were calculated using cardiologist-confirmed findings from a subsequent one-month school-based screening of 440 students. Results: The mean pre-test score was 64±11, significantly increasing to 95±7.5 after training (p<0.001). Image quality was diagnostically adequate in 97.7% of examinations. Sensitivity and specificity of GP-acquired screening echocardiograms were 41.4% (95% Confidence Interval/CI: 29.9%-53.0%) and 73.7% (95% CI: 69.1%-78.3%), respectively. No significant differences in scores were observed by gender or age group. Conclusion: Although participants initially had limited exposure to echocardiography, the structured short-term curriculum substantially improved knowledge, image acquisition skills, and screening capability. Task-shifting echocardiographic screening to mid-level providers appears feasible in Indonesia and warrants further refinement and scale-up.